A segmentation study of college students based on employer choice preferences - Erel, Sarhan. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2011., 2011)
This study tries to determine the important job related attributes for college students during their employer selection process. In doing so, college students are classified into three general groups, or clusters, with respect to their common and most important preferences of job attributes. Various demographic characteristics of each group is identified and discussed. The questionnaire was prepared based on a literature research and applied to 111 college students in Bogazici University during 2010 - 2011 semester. Basic descriptive statistics tools, two-step cluster analysis and statistical hypotheses testing methods were utilized to analyze the resulting data. Collected data were analyzed to identify three distinct groups of college students with respect to their common job attributes preferences. Six categorizing variables, considered to affect the students’ preferences, have been included in the analysis: seniority level, department of study, gender, size of the city they have been raised in, family income level and parents’ education level. Three distinct clusters have been obtained. Cluster characteristics and corresponding preferences were identified and tabulated. In addition, six hypotheses were formed to see the possible effect of some of these independent variables on students’ preferences on job attributes. The analysis showed that while family income level do not provide a clear understanding of student preferences, seniority level, department of study, city size and gender signal the direction of students’ preferences for some job related attributes during an employer selection process.
Keywords: Job hunting.; Vocational guidance.